Caso para diagnóstico Case for diagnosis - Mônica Santos; Carolina Talhari; Lisiane Nogueira; Renata Fernandes Rabelo; Luiz Carlos de Lima Ferreira; Sinésio Talhari (Sociedade Brasileira de Dermatologia, 2010)
Desde as primeiras descrições da aids, no início da década de 1980, a infecção herpética é vista como uma das doenças oportunistas mais prevalentes em pacientes com retrovirose. A infecção pelo herpes-vírus simples tipo 2, agente etiológico de 60 a 90% dos casos de herpes genital, é bastante comum em pacientes com aids. O acometimento mucocutâneo pelo herpes-vírus simples tipo 2 pode ser grave e prolongado (persistente por mais de um mês), sendo caracterizado como doença definidora de aids. Since the first reports and descriptions of AIDS in the early 1980s, herpetic infection has been considered as one of the most prevalent and opportunistic aids related infections in patients with retroviral diseases Infection by Herpes simplex type 2 (HSV-2), the etiologic agent responsible for 60% to 90% of the cases of genital herpes, is very common among patients suffering from AIDS. Herpes simplex type 2 infection may cause severe and prolonged (over a period of time of one month) mucocutaneous onset of the disease, being characterized as an aids defining clinical condition.